Incidence and mortality of alcohol-related hepatitis in Denmark – an update, 2016–2023 - Khaibar Ghulam Hazrat; Sidsel Hyldgaard Støy; Thomas Damgaard Sandahl; Peter Jepsen (JHEP Reports)
Background & Aims: Alcohol-related hepatitis (AH) is a severe liver disease associated with high mortality. This study provides data on the incidence and mortality of AH in Denmark from 2016 to 2023. Methods: We identified all patients with a first-time hospital discharge diagnosis of AH and a serum bilirubin level >3 mg/dl in 2016–2023. We computed the standardized incidence rate of AH in the Danish population and mortality from admission with AH. We compared the results to our previously published findings for the 1999-2008 period. Results: We included 1,016 patients with a median age of 54.7 years (66% men). The standardized incidence rate was 21.7 per million per year, which remained stable during the study period for both men and women. Mortality was high: 18% at 28 days, 26% at 84 days, and 40% at 365 days. Although 28-day and 84-day mortality risks were lower in 2023 compared to earlier years, no overall trend of improvement was observed. The median MELD score at admission, available for 846 patients, was consistently high at 26, and 75% had severe AH (MELD >21). Compared to an incidence rate of approximately 45 per million per year in 2009, the incidence of AH has since decreased dramatically, mirroring Danish alcohol sales. Conclusions: The incidence of AH in Denmark markedly declined from 2009 but stabilized between 2016 and 2023. Mortality remains high, emphasizing the need for better treatment strategies. Impact and implications: This study investigated the incidence and mortality of alcohol-related hepatitis (AH) in Denmark from 2016 to 2023, providing updated data in the context of declining alcohol consumption. While AH incidence has decreased since 2009, mirroring reduced alcohol intake, it has stabilized in recent years, and mortality remains high. These findings highlight the ongoing burden of AH for healthcare providers, researchers, and policymakers. Our results can support early interventional strategies, guide clinical management, and reinforce public health efforts to reduce alcohol consumption. Limitations, such as the lack of detailed treatment data, should be considered to avoid overgeneralization.